Borderline Dysplastic Hips Undergoing Hip Arthroscopy Achieve Equivalent Patient Reported Outcomes When Compared With Hips With Normal Acetabular Coverage: A Systematic Review and Meta-Analysis. Issue 6 (15th March 2023) - Krivicich, Laura M.; Rice, Morgan; Sivasundaram, Lakshmanan; Nho, Shane J.
Abstract : Purpose: To systematically review and meta-analyze studies reporting lateral center edge angle as it relates to patient-reported outcome (PRO) measures and clinically notable outcome assessments for patients undergoing hip arthroscopy for femoroacetabular impingement syndrome or labral pathology with borderline dysplastic hips (BDH). Methods: PubMed, EMBASE, and the Web of Science Core Collection databases were queried for articles evaluating lateral center edge angle as a predictor of PRO after hip arthroscopy. Articles were eligible for meta-analysis if they compared PROs measures between patients with normal acetabular coverage and borderline dysplasia and were at least level III evidence. Continuous random-effects models with standardized mean differences were used to compare postoperative Hip Outcome Score—Activities of Daily Living and sports subscales, modified Harris Hip Score, international Hip Outcome Tool scores, Satisfaction, and Visual Analog Scale Pain scores between normal coverage and borderline dysplastic groups. Results: Overall, 989 hips undergoing arthroscopy from six investigations were included in this meta-analysis, including 315 borderline dysplastic subjects (mean age 27.5 years) and 674 subjects with normal coverage (mean age 26.9 years). Borderline dysplastic and normal coverage cohorts were followed for an average of 37.0 and 36.8 months, respectively. Postoperative PRO measures (Hip Outcome Score—Activities of Daily Living, Hip Outcome Score-Sports Subscale, modified Harris Hip Score, international Hip Outcome Tool-12, Satisfaction, and Visual Analog Scale Pain) collected approximately three years after hip arthroscopy were not markedly different between subjects with BDH when compared with patients with normal coverage. Conclusions: In a meta-analysis of the available literature, patients with BDH are able to equally reach statistically similar clinical outcomes after isolated hip arthroscopy as compared with control subjects without dysplasia at short-term follow-up. A BDH should not be considered a contraindication to hip arthroscopy when optimal PRO achievement is the goal. Level of Evidence: Level III, Systematic Review and Meta-Analysis.